PENGARUH KEPEMILIKAN PERUSAHAAN TERHADAP PENETAPAN BIAYA AUDIT - Aulia Rachma Hanifah; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the effect of management ownership structure, foreign ownership, and Government Ownership Foreign Ownership as an independent variable on audit fees as the dependent variable on companies listed on the Indonesia Stock Exchange LQ45. The population used in this study were 34 companies listed on the Indonesia Stock Exchange LQ45 (IDX) during the 2016-2018 period in a row. The sample used was as many as 27 companies using purposive sampling techniques with the criteria of having an annual report and financial statements during the study period. Analysis of research conducted using multiple linear regression analysis by first passing the classical assumption test and using the t test, F test, and the coefficient of determination (R2) to determine the significance and influence of management ownership, foreign ownership, and Government Ownership Foreign ownership of costs an audit. The results of this study indicate that there is a significant positive effect on the variable foreign ownership of audit fees. Managerial and government ownership does not have a significant negative effect on audit fees. Overall, the ownership structure has a different effect on audit fees